The Thai version of the COVID-19 Yorkshire Rehabilitation Scale: a valid instrument for the psychometric assessment of the community members in Bangkok, Thailand - Suphamas Partiprajak; Suphanna Krongthaeo; Noppawan Piaseu; Jatuporn Wongsathikun; Anon Kongsuwan (BMC, 2023)
Abstract Background Coronavirus disease 2019 (COVID-19) can develop into a long-term COVID in some cases, which can have a major impact on various health systems requiring appropriate treatment involving multi-disciplinary healthcare. The COVID-19 Yorkshire Rehabilitation Scale (C19-YRS) is a standardized tool widely used for screening the symptoms and severity of long-term COVID. Translation of the English version of the C19-YRS into the Thai language and testing it is essential for the psychometric evaluation of the severity of the long-term COVID syndrome prior to providing rehabilitation care for community members. Methods Forward-and back-translations including cross-cultural aspects were conducted in order to develop a preliminary Thai version of that tool. Five experts evaluated the content validity of the tool and produced a highly valid index. A cross-sectional study was then conducted on a sample of 337 Thai community members recovering from COVID-19. Assessment of internal consistency and individual item analyses were also performed. Results The content validity resulted in valid indices. The analyses showed that 14 items had acceptable internal consistency, based on the corrected item correlations. However, five symptom severity items and two functional ability items were deleted. The Cronbach's alpha coefficient of the final C19-YRS was 0.723, indicating acceptable internal consistency and reliability of the survey instrument. Conclusions This study indicated that the Thai C19-YRS tool had acceptable validity and reliability for the evaluation and testing of the psychometric variables in a Thai community population. The survey instrument also had acceptable validity and reliability for screening the symptoms and severity of long-term COVID. Further studies are warranted in order to standardize the various applications of this tool.